Children in Digital Age – Croatian Perspective - Lisičar, Hrvoje (Children in Digital Age, 2025)
Abstract:Today, it is difficult to imagine life without digital technology and the Internet. They have become an integral part of our everyday lives, especially the lives of children and young people. Children use the Internet for learning, entertainment, communication, creativity and to express themselves. Digital technology and especially the Internet gives them access to a variety of information, services and opportunities that can enrich their childhood, development, and well-being. However, the digital environment also carries numerous challenges and risks for children’s rights. Children can be exposed to violence, abuse, exploitation, explicit sexual content, hate speech, misinformation and disinformation, various other types of manipulation and other harmful content on the Internet. Children may also face violations of their right to privacy, dignity, identity, and participation in the digital environment. They can be discriminated against or excluded because of lack of access, equipment, skills or support to use digital technology. Therefore, it is important to ensure that children have the same rights and protections in the digital environment as they have in our everyday lives. This implies respect, exercise and protection of all children’s rights established by the Convention on the Rights of the Child and other international and national documents. It also implies involving children in decision-making and policies that affect their lives in the digital age. In Croatia, there are numerous actors and initiatives that deal with issues of children’s rights in the digital environment. Among them are state bodies, non-governmental organisations, academic institutions, the media and the business sector. They carry out various activities, such as education, prevention, counselling, research, advocacy and monitoring, to promote and protect children’s rights in the digital world. This chapter aims to provide an overview of children’s internet use in Croatia; this includes the legal framework for the protection of children’s rights in the digital age together with definitions of legally relevant terms in national legislation as well as some examples of judicial practice and discussion about rights to privacy, to be forgotten, to access to information, to education, to be safeguarded from abuse, to freedom of expression, and to be heard. Keywords: children’s rights, digital environment, children and the Internet, digital age, information society and children, social media, audiovisual medial services, video-sharing platforms, media literacy